THE INFLUENCE OF ORGANIZATIONS ENGAGEMENT AND LEARNING ACHIEVEMENT ON WORKING READINESS OF DEVELOPMENT ECONOMICS DEPARTMENT STUDENT CLASS OF 2017 UNIVERSITAS NEGERI MALANG - Ashif Chumaida Sari; Nasikh Nasikh; Grisvia Agustin (Cita konsultindo, 2022)
This study aims to the influence of organizations engagement and learning achievement on working readiness of development economics department student class of 2017 Universitas Negeri Malang. The research method uses descriptive quantitative. The population of this research is all of student of the Development Economics Department class of 2017, Universitas Negeri Malang. The technique used sampling is simple random sampling. This study used a sample of students with indications of being active in organizations. The instruments used are quistionnaires and documentation. The result of the study show that adjusted R square value of 0.424, it can be stated that organizations engagement and learning achievement contributed 41.9% to the work readiness of students of Development Economics Department class of 2017, Universitas Negeri Malang. While 58.1% is explained by other variables not examined in this study.